Penicillinase producing Neisseria gonorrhoeae from St Thomas' Hospital 1976-1990–the first fifteen years. Issue 3 (June 1993) - Warren, C; Phillips, I
Abstract : OBJECTIVE–To examine the penicillinase producing N. gonorrhoeae (PPNG) collected at St Thomas' Hospital from 1976-1990 and, by determination of antibiotic susceptibility pattern and application of three typing methods, examine the prevalence of different gonococcal types. Also to determine whether there is any relationship between antibiotic sensitivity, plasmid profile, auxotype and serovar. MATERIALS AND METHODS–A total of 665 isolates of PPNG from patients attending the Department of Genitourinary Medicine at St Thomas' Hospital were characterised by antibiotic MIC, plasmid profile, auxotyping and serotyping. RESULTS–Penicillin MICs for 85% of all isolates were between 0.25 and 32 mg/l. The MIC of tetracycline for 60-80% of the isolates was < 1 mg/l. A small number of isolates had tetracycline MICs of 32 mg/l but MICs > 32 mg/l were not seen. Over 90% of the isolates were sensitive to the remaining three antibiotics tested, erythromycin, cefuroxime and spectinomycin. The 3.2 or 4.4 MDa plasmid with or without the 24.5 MDa conjugal plasmid was seen in all isolates until 1989/90 when a 2.9 MDa beta-lactamase encoding plasmid and the 25.2 MDa plasmid mediating tetracycline resistance were also recognised. Ninety-nine percent of all isolates belonged to one of four auxotypes, prototrophic, arginine, proline or proline/arginine requiring. An initial predominance of isolates with the 1A outer membrane protein was reversed in 1982 and 1B has remained predominant. Thirty two different serovars were identified among the 665 isolates, 14 belonged to serogroup 1A and 18 to 1B, and the eight most common accounted for 83.9% (554) of all isolates. Analysis of the results of combined typing methods showed there was an association between antibiotic resistance, plasmid profile and serogroup. The number of auxotypes and serovars detected in the collection, indicates the possibility that PPNG have been introduced from abroad or outside our local population. CONCLUSION–Temporal trends in the distribution of auxotype/serovar classes show that the total population of PPNG isolates is formed by a heterogenous mixture in which certain auxotype/serovar classes appear, disappear and may re-emerge. Others were present throughout in small numbers.